Assessment on the state of integrated water resources management in the Laguna de Bay region - Morales, Charlene Chris R.; Tabios, Guillermo Q. III (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
Water is essential to human life, drives economic development, and sustains the ecosystems and environment. Water is both a social and economic good. With various competing usesof water, water availability and security is threatened, conflicts inevitably arise, and there is a growing need for a more efficient way to manage water resources. The Integrated Water Resources (IWRM) is a water governance approach which emphasizes the importance of horizontal and vertical organizational structures of stakeholders in decision-making. The main objective of the study is to assess the state of IWRM implementation in the Laguna de Bay Region. The assessment was made with the use of indicators that assigns a quantitative value to the qualitative nature of IWRM. The indicators were selected and modified from global networks and initiatives that advocate the use of IWRM and the river basin approach. A total of 26 indicators were used for the assessment. While primarily an assessment tool, the indicators allow for a monitoring system, identify the problem areas, and communicate the progress made through the application of strategies. The set of indicators chosen indicated a score of 58.14, few points away from what the index has dictated to be Medium-High. The score may also be interpreted in two ways, through the IWRM component, or through the level of the study. The IWRM component that received the lowest score was Institutional Arrangements (48.00), followed by Enabling Environment (59.33), and lastly, Managing Instruments (67.08). Meanwhile, the IWRM assessment at the national level scored 59.11, and the river basin level or Laguna de Bay region scored 57.17. The score signifies that there are efforts in implementing IWRM in the country and in the Laguna de Bay region, but they lack strength of legislation, institutional strength, and management instruments, to be truly effective. A strengthened monitoring and evaluation system, and updating of current water laws and governance structure is recommended.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Integrated water development -- Laguna de Bay -- Philippines